Desmopressin Acetate and Nocturnal Enuresis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
A literature review of 18 randomized controlled trials of desmopressin for resistant enuresis involving 689 patients is reported from the University of Manitoba, Canada.